2007
DOI: 10.2967/jnumed.107.042192
|View full text |Cite
|
Sign up to set email alerts
|

The Dental Safety Profile of High-Dose Radioiodine Therapy for Thyroid Cancer: Long-Term Results of a Longitudinal Cohort Study

Abstract: The long-term dental safety profile of high-dose radioiodine therapy remained elusive despite more than 6 decades of clinical use. Methods: In a cohort study, we investigated the incidence of sialadenitis, xerostomia, caries, and tooth extractions after high-dose radioiodine therapy for differentiated thyroid cancer and explored risk factors by multiple regression models. Results: One hundred seventy-six participants were recruited (median follow-up, 6.6 y; range, 1.1-32.6 y; patient-years: 8,472 before and 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
38
0
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 17 publications
0
38
0
7
Order By: Relevance
“…Recent reviews of adverse salivary effects after 131 I therapy have indicated an incidence of acute sialadenitis ranging from 24% to 67%, with chronic sialadenitis in 11%243% of those treated (2,8,9). Clinically relevant xerostomia, with dry mouth, swallowing difficulties, and a loss of taste, has, to a certain extent, impaired the quality of life of thyroid cancer patients (2,(4)(5)(6)(7)(8)(9). Therefore, prevention of salivary gland injury in 131 I therapy becomes an important issue.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reviews of adverse salivary effects after 131 I therapy have indicated an incidence of acute sialadenitis ranging from 24% to 67%, with chronic sialadenitis in 11%243% of those treated (2,8,9). Clinically relevant xerostomia, with dry mouth, swallowing difficulties, and a loss of taste, has, to a certain extent, impaired the quality of life of thyroid cancer patients (2,(4)(5)(6)(7)(8)(9). Therefore, prevention of salivary gland injury in 131 I therapy becomes an important issue.…”
mentioning
confidence: 99%
“…Salivary glands are highly radiosensitive (3). Radiation sialadenitis and xerostomia have become the most frequent complication of high-activity 131 I therapy for thyroid cancer (2,(4)(5)(6)(7)(8)(9). Additionally, salivary gland injury can be observed even when the administered 131 I activity is relatively low (7)(8)(9).…”
mentioning
confidence: 99%
“…Ongoing sialoadenitis can lead to atrophy of the secretory parenchyma and salivary gland fibrosis, which may result in decreased saliva flow rates (hyposalivation), sensation of a dry mouth (xerostomia), and an increased risk of oral infections and dental caries (7 ). A further loss of salivary gland function due to stem cell damage may become clinically manifest after 60-120 d, because this time is specific for salivary cell turnover (8).…”
mentioning
confidence: 99%
“…Recent reviews of adverse effects of 131 I therapy on salivary glands cite incidences of acute sialadenitis from 24% to 67% and of chronic sialadenitis from 11% to 43% (3)(4)(5)19). Clinically relevant xerostomia is characterized by a dry mouth, swallowing difficulties, and a loss of a sense of taste, and markedly impairs quality of life after 131 I therapy (19)(20)(21). Thus, the prevention of salivary gland dysfunction by 131 I is clinically important and methods to prevent this dysfunction are urgently required.…”
Section: Discussionmentioning
confidence: 99%